1986
DOI: 10.1007/bf01661286
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion of ofloxacin into the cerebrospinal fluid in patients with bacterial meningitis

Abstract: Ofloxacin diffusion into cerebrospinal fluid (CSF) was evaluated in nine patients with bacterial meningitis. Patients were under treatment with i.v. amoxicillin (100 mg/kg/day), and during the first five days they were also given oral ofloxacin, 200 mg b.i.d. On days 2 and 5, blood and CSF samples were collected for assays by both HPLC and microbiological techniques. Samples were obtained 2 h (n = 2), 4 h (n = 1), 6 h (n = 2), 8 h (n = 2) and 12 h (n = 2) after the ofloxacin dose respectively. Concentration in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…Drancourt et al (3) found concentrations in CSF of 0.1 to 2.0 ,ug/ml 3 h after a 300-mg oral dose in patients with lymphocytic meningitis and 1.0 to 2.8 pug/ml in patients with purulent meningitis. Another report (13) studied nine patients with acute purulent meningitis who received 200 mg orally twice a day. After a few days of treatment, ofloxacin was measured in CSF and ranged from 0.9 to 4.5 jig/ml, corresponding to a penetration of 50 to 60%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Drancourt et al (3) found concentrations in CSF of 0.1 to 2.0 ,ug/ml 3 h after a 300-mg oral dose in patients with lymphocytic meningitis and 1.0 to 2.8 pug/ml in patients with purulent meningitis. Another report (13) studied nine patients with acute purulent meningitis who received 200 mg orally twice a day. After a few days of treatment, ofloxacin was measured in CSF and ranged from 0.9 to 4.5 jig/ml, corresponding to a penetration of 50 to 60%.…”
Section: Discussionmentioning
confidence: 99%
“…The penetration of ofloxacin and other fluoroquinolones in the cerebrospinal fluid (CSF) has been studied in inflamed and noninflamed meninges from a small number of patients, and the concentrations were found to be higher than the MICs for most susceptible gram-negative bacilli (2,3,13,14).…”
mentioning
confidence: 99%
“…The new Table IV. Penetration of the fluoroquinolones into the CSF 105 fluoroquinolones penetrate well into the CSF: the ratio of more than 50% in the case of inflamed meninges is superior to that of the {:1-lactams (Stahl et al 1986). The half-life in CSF is similar to that in plasma.…”
Section: Penetration Into the Csfmentioning
confidence: 97%
“…The CSF penetration of quinolones was studied by several authors, both in patients with noninflamed and in patients with inflamed meninges (Bassaris et al 1986;Dow et al 1986;Kitzes-Cohen et al 1986;Stahl et al 1986;Stiibner et al 1986;Valainis et al 1986;Wolff et al 1984). The data suggest that quinolones penetrate faster into the CSF of patients with meningeal infections compared with non-infected patients.…”
Section: Cerebrospinal Fluidmentioning
confidence: 98%